Squamous Cell Carcinoma of the Oral Tongue in Two Patients Previously Exposed to Long-Term Pegylated Liposomal Doxorubicin - Bonomi, Marcelo R. (AlphaMed Press, 2012)
Two cases of squamous cell carcinoma possibly related to exposure to pegylated liposomal doxorubicin are presented.